Mobilization of CD34+CXCR4+ Stem/Progenitor Cells and the Parameters of Left Ventricular Function and Remodeling in 1-Year Follow-up of Patients with Acute Myocardial Infarction - Rafał Wyderka; Wojciech Wojakowski; Tomasz Jadczyk; Katarzyna Maślankiewicz; Zofia Parma; Tomasz Pawłowski; Piotr Musiałek; Marcin Majka; Marek Król; Wacław Kuczmik; Sebastian Dworowy; Barbara Korzeniowska; et al. (Hindawi Limited, 2012)
Mobilization of stem cells in acute MI might signify the reparatory response. Aim of the Study. Prospective evaluation of correlation between CD34+CXCR4+ cell mobilization and improvement of LVEF and remodeling in patients with acute MI in 1-year followup. Methods. 50 patients with MI, 28 with stable angina (SAP), and 20 individuals with no CAD (CTRL). CD34+CXCR4+ cells, SDF-1, G-CSF, troponin I (TnI) and NT-proBNP were measured on admission and 1 year after MI. Echocardiography and ergospirometry were carried out after 1 year. Results. Number of CD34+CXCR4+ cells in acute MI was significantly higher in comparison with SAP and CTRL, but lower in patients with decreased LVEF ≤40%. In patients who had significant LVEF increase ≥5% in 1 year FU the number of cells in acute MI was significantly higher versus patients with no LVEF improvement. Number of cells was positively correlated (𝑟=0,41,𝑃=0,031) with absolute LVEF change and inversely with absolute change of ESD and EDD in 1-year FU. Mobilization of CD34+CXCR4+ cells in acute MI was negatively correlated with maximum TnI and NT-proBNP levels. Conclusion. Mobilization of CD34+CXCR4+ cells in acute MI shows significant positive correlation with improvement of LVEF after 1 year.